Olfactory dysfunction with traumatic brain injury and posttraumatic-stress symptoms in post-deployed military personnel - Shura, Robert D.; Pickett, Treven C.; Powell, Jacob; Yoash-Gantz, Ruth; McDonald, Scott D.; Walker, William C.; Rowland, Jared A.; Tupler, Larry A. (Frontiers in Neurology, 2025)
IntroductionPrior research suggests that olfactory dysfunction may occur following a traumatic brain injury (TBI) due to structural injury to the olfactory peripheral or central networks. Olfaction may also be affected in posttraumatic stress disorder (PTSD) due to traumatic re-experiencing. Given the relevance of both TBI and PTSD to the military and veteran populations, the purpose of this study was to evaluate whether the University of Pennsylvania Smell Identification Test (UPSIT) would be useful in differentiating TBI from significant PTSD symptom burden in a sample of post-deployed active-duty military and veterans.MethodsA sample of 276 participants with UPSIT data and passing scores on validity measures completed a larger study on neurocognition of predominantly post-deployed veterans of the wars in Afghanistan and Iraq. TBI history was ascertained by medical records or a self-report questionnaire; PTSD symptoms were measured using the PTSD Checklist-Military version (PCL-M) and the Traumatic Stress scale (ARD-T) of the Personality Assessment Inventory. Those with a history of TBI (+TBI) were compared with those without (–TBI) on total UPSIT score; severity of injury and number of injuries were also evaluated. Furthermore, those with and without significant PTSD symptoms (+PTSD and –PTSD) were compared on UPSIT total scores. Finally, group comparisons were conducted to assess whether PTSD demonstrated a significant effect above and beyond TBI.ResultsHistory of TBI was associated with lower UPSIT scores (–TBI M = 34.02, +TBI M = 32.76, z = −2.38, p = 0.017, r = 0.14); however, the effect size was small and driven by the difference between moderate/severe TBI and –TBI (moderate/severe M = 31.78). Number of mild TBIs was not associated with UPSIT scores: The presence of PTSD symptoms and symptom clusters were not significantly associated with UPSIT scores. PTSD symptoms showed no additional effects on poorer olfaction scores above and beyond TBI.DiscussionOlfactory identification was significantly reduced in those with a history of TBI, suggesting that olfaction may be useful in the assessment of these individuals for potential treatment needs. Veterans with significant PTSD symptoms, however, did not display different olfactory ability compared with those without, regardless of TBI status.